The Influence of The Role of Internal Auditors, Performance of Internal Auditors and Effectiveness of Internal Control Systems on Company Performance in People's Credit Banks in Jember District - Ronalin, Gustina; Yulinartati; Rendy Mirwan Aspirandi (Westscience Press, 2024)
BPR is a financial institution, one of which collects public funds in such a way that it must follow the principles of prudence and good governance in its operations. In accordance with Regulation (POJK) number 4/POJK.03/2015 concerning the Implementation of BPR Management, sanctions are given to BPRs that do not comply with these provisions. This research aims to determine the influence of the role of internal auditors, the performance of internal auditors and the effectiveness of the internal control system on company performance at Rural Banks in Jember Regency. This research uses primary data in the form of questionnaires and secondary data in the form of previous research and BPR data accessed via the OJK website/Perbarindo website. The respondents of this research were 30 internal auditors who worked at BPR Jember Regency. The sample determination method is based on purposive sampling. The data analysis technique uses a multiple linear regression model. The results of this research show that the role of internal auditors has a positive and significant effect on company performance, the performance of internal auditors has a positive and significant effect on company performance, and the effectiveness of the internal control system has a positive and significant effect on company performance.